Analysis Of Land Subsidence Relationship With Groundwater Table Depletion In South Jakarta - Nembo, Andreas Julio; Anugrahadi, Afiat; Fitra Yuda, Himmes (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2023)
Increased development activities and urbanization in South Jakarta have increased groundwater extraction. Continuous withdrawal of groundwater with poor management can cause a decrease in the groundwater level and trigger a subsidence. Therefore, a study is needed regarding the relationship of land subsidence with the decrease in groundwater levels that occur in South Jakarta. This research was conducted using secondary data in the form of drill log data to determine subsurface lithology, land subsidence measurement data using the GPS geodetic method, and groundwater level data in monitoring wells in Jakarta. The results of the study show that surface sediment deposits are dominated by a layer of clay which is still unconsolidated and relatively thickened to the north with a thickness of more than 300 m. This condition shows that the sediment layers in Jakarta are still undergoing a compaction process so that naturally subsidence occurs in the soil surface. Subsidence in the land surface in South Jakarta has a fairly strong correlation with the decline in the groundwater level, which is equal to 0.504, which means it has a fairly strong degree of correlation of 50.4%.